Characteristics of Post Partum Hemorrhage (HPP) in Mothers at Dr. Hospital. M. Djamil Padang 2019-2022 - Fegita, Primadella; Anwar, Husnul Khotimah (Formosa Journal of Sustainable Research, 2024)
Hemorrhagic Postpartum hemorrhage (HPP) is bleeding that exceeds 500 milliliters after the baby is born in vaginal delivery and 1000 milliliters in cesarean section. Severe post partum hemorrhage causes around 25% of maternal deaths globally. The incidence of HPP in Indonesia in WUS is around 5.3%. Risk factors for HPP are close birth spacing, parity, maternal age during pregnancy, low hemoglobin levels, pregnancy and macrosomia. To determine the characteristics of the incidence of HPP in mothers at RSUP Dr. M. Djamil Padang 2019-2022. Categorical descriptive research using a cross sectional design. The sampling method was consecutive sampling. HPP occurred most frequently based on etiology, namely retained placenta in 24 cases (44.4%), hemoglobin level <11 grams in 48 cases (88.9%), maternal age 20-35 years in 33 cases (61.1%), Parity, namely multiparity, was 27 cases (50%), baby weight ≤400 grams was 49 cases (90.7%), and birth interval was ≥2 years, 40 cases (74.1%). Most HPP patients are caused by retained placenta, mothers with hemoglobin levels <11 grams, mothers aged 20-35 years, mothers with multiparity, mothers whose babies weigh ≤4000 grams, and mothers who have birth intervals ≥2 years